Evaluation of Oxidative Stress activity, DNA Damage and Global DNA Methylation among Patients with Chronic Kidney Disease - Hamid, Rehab Harith; AL-Jumaily, Rakad M. Kh (Iraqi Journal of Science, 2024)
Chronic kidney disease (CKD) is a serious threat to global medicine as more than two million get CKD yearly. However, the understanding of DNA damage, DNA methylation in chronic kidney disease (CKD) remains elusive. The study goal was to establish whether homocysteine (Hcy), oxidative DNA damage (ODD), glutathione peroxidase (GPX3) and 5-methylcytosine (5mC) could be used as a potential marker of CKD. Measurements of Hcy, ODD, and GPX3 levels were done by commercial enzyme linked immunosorbent assay (ELISA) kits of 60 patients with chronic kidney disease (age range 20-87 years) and 30 age-matched healthy controls. DNA extracted from blood of patients was used to evaluate the global 5-methylcytosine (5mC) levels by the MethylFlashTM methylated DNA quantification Kit (Epigentek, USA). Results indicated a highly significant rise in Hcy and ODD in CKD patients in contrast to the healthy controls group. Although GPX3 level reduced in CKD patients, there was no significant difference between the patients and healthy controls. This research results also revealed significant rise in global 5mC level in CKD patients in comparison to the healthy controls. There is a potential role of homocysteine, oxidative DNA damage and global 5mC to be used as a biomarker for the progression of CKD.